Charles Robert "Bert" Kelly interviewed by Stewart Cockburn - Kelly, C. R. (Charles Robert), 1912-1997.; Cockburn, Stewart, 1921-2009. (1992)
Mr Kelly speaks of the Charles Hawker awards; Lilias Needham's view of Hawker; the Kelly's relationship with the Hawkers; Hawker and his father's being wounded in World War I; entry into "agro-politics"; his father's involvement with the Tariff Board; tariffs and employment; Hawker's stoicism; Hawker's interest in Kelly's children; Hawker's interest in farming; the plantation in honour of Hawker; Hawker as an Australian; Hawker's attitude to his disabilities; the way Hawker helped people; Dick Butler's standing for a seat; Hawker as a possible Prime Minister.
Charles Hawker was a pastoralist, soldier and Federal Parliamentarian killed in a DC3 aircraft crash in Victoria in 1938.
Also available online
Charles Kelly was Minister for the Navy 1968-69, and for Works 1967. He was Liberal Member of the House of Representatives for Wakefield, S.A. 1958-78.
Transcript: (17 leaves)
Keywords: Hawker, Charles, -- 1894-1938 -- Interviews